One of the Five Islands, Trinidad, B.W.I. - (:unkn) unknown (D.Adamson,[Trinidad and Tobago], 2011)
The postcard shows Rock Island which belongs to the group of "Five Islands" which are actually a group of six islands located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. They are also known as Las Cortorras. Rock Island is the second smallest island in the group.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Vacation homes--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Bodies of water--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture, Domestic--Trinidad and Tobago; [1900]; Five Islands, The